P1_10 Solar propulsion - Morland-Nuttall, Thomas; Fox, Adam; Evans, Daniel; Bowes-Reynolds, John (Physics Special Topics, 2021)
Solar sails and electric sails are proposed methods of spacecraft propulsion, they both use particles from the Sun to produce this thrust. But, to produce thrusts equivalent to modern ion engines (0.5 N)[4] a solar sail would need to be $54,900 m^2$ and an electric sail would need to have $8.33 × 10^6 m$ of wire, this makes both methods only practical for light spacecraft.